Construction of a novel photoelectrochemical sensor for detecting trace amount of copper (II) ion. (20th February 2021) - Chen, Jiexia; Zhao, Guang-Chao; Wei, Yan; Feng, Dexiang; Zhang, Hailong
Highlights: A novel and sensitive photoelectrochemical sensor for detecting copper (II) ion was developed. Its signal sensing strategy was based on the formation of the polydopamine-copper (II) complex (PDA-Cu (II)), which could attach tightly to the surface of ITO electrode. The sensor displayed with a linear range of 1–1000 pM and a detection limit as 0.45 pM. Abstract: A photoelectrochemical (PEC) sensor for determination of copper (II) ion has been developed. The indium tin oxide (ITO) electrode modified by ZnS quantum dots (QDs) was used as working electrode and dopamine (DA) as detection solution. When different amounts of Cu 2+ were added, the polydopamine-copper (II) complex (PDA-Cu (II)) was in suit formed and attached tightly to the surface of ITO electrode based on the interaction between copper (II) and dopamine (DA) under weakly alkaline (pH 8.00) solution. The detection of Cu 2+ was achieved by means of the decreasing photocurrent. The linear range of 1 - 1000 pM and sensitivity of 0.45 pM were obtained. In addition, the formation of PDA-Cu (II) was characterized by Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS). Thus, a PEC sensor based on the change of electrode surface state can realize the sensitive detection of Cu 2+ . Graphical abstract: Image, graphical abstract